Brain-Based Learning and Its Impact on High School Students' Self-Efficacy and Anxiety - Jafari, Amir Hassan; Miri, Mahdiyeh Sadat; Rahardi, Gilang Tris; Wahid, Najihah Abd (BIRCU, 2025)
Brain-Based Learning (BBL) has been widely researched due to its ability to potentially improve cognitive processing, decrease anxiety and increase self-efficacy in the classroom. The impact of BBL strategies on high school students' academic confidence and mental well-being: A study. Using a quasi-experimental design, we analyze the effects of BBL relative to customary teaching practices. The results indicate that BBL is, indeed, an effective pedagogical approach, significantly enhancing self-efficacy and decreasing anxiety in students. The paper also considers implications for educators, policymakers, and future research directions.